Answer:
C
Step-by-step explanation:
Answer:
its C
Step-by-step explanation:
let h = horse, let c = cow, let p = pig
so,
hcp
hpc
cph
chp
phc
pch
so, that is 6 different ways she can arrange it.
pig, cow, horse
pig, horse, cow
horse, pig, cow
horse, cow, pig
cow, pig, horse
cow, horse, pig
Answer:
Using 3.14 for pi
835.24 cm^2
Using the pi button for pi
835.6636459 cm^2
Step-by-step explanation:
The surface area of a cylinder is given by
SA = 2 pi r^2 + 2 pi r h
= 2 * pi ( 7)^2 + 2 pi ( 7) * 12
= 98 pi + 168 pi
=266 pi
Using 3.14 for pi
835.24 cm^2
Using the pi button for pi
835.6636459 cm^2
Answer:
226 or 835.664
Step-by-step explanation:
Surface area of a right cylinder= 2πrh+2πr^2
=2π7✖️12+2π49
=226π
Hope this helped, and have a nice rest of your day!
Answer:
is false statement.
B is correct
Step-by-step explanation:
is reflected across line L to form .
If we join A and and intersect line L at point D.
Reflection: A transformation of a geometric figure such that creating a mirror image across the line. The line of reflection is called axis of reflection.
As we know mirror image figure has same property their side measure and angle measure equal.
.
Distance of each vertex of figure from axis of reflection line is equal to their corresponding vertex.
Therefore, True statements are:-
Please find the attached figure for reflection and coordinates.
Hence, is false statement.
where is the mistake and what should be done differently?
Step-by-step explanation:
a) There's a mistake at the third step from the beginning.
b) Instead of adding 25 , Josh added 100. While solving an equation using "Completing Squares Method" , we need to write the L.H.S. in the form of or , so that in the next step it can be converted into or .
c)
Taking -88 to R.H.S. , it's sign changes and becomes +88.
Using "Completing Squares Method" , L.H.S. can be written as :-
s+1/4 = 4/8
s=
Answer:
8 = 16
Step-by-step explanation:
1/4 = 4 /8
Cross multiply:
1 * 8 = 4 * 4
Simplifying
1 * 8 = 4 * 4
Multiply 1 * 8
8 = 4 * 4
Multiply 4 * 4
8 = 16
Solving
8 = 16
a - 6b + 4c
a - 10b + 4c
-a + 10b + 4c
Answer:
a-6b+4c
Step-by-step explanation:
a-{5b-[a-(3b-2c)+c-(a-2b-c)]}
a-{5b-[a-1(3b-2c)+c-1(a-2b-c)]}
a-{5b-[a+(-3b+2c)+c+(-a+2b+c)]}
a-{5b-[a-3b+2c+c-a+2b+c]}
a-{5b-[-b+4c]}
a-{5b+[b-4c]}
a-{5b+b-4c}
a-{6b-4c}
a+{-6b+4c}
a-6b+4c